ANALISIS FARMAKOKINETIK, TOKSISITAS DAN DRUG-LIKENESS LIMA SENYAWA AKTIF BIJI PINANG SEBAGAI ANTIDEPRESAN SECARA IN SILICO - Riryn Novianty (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2023)
This study aims to screen the potential of five active compounds in areca nut L-phenylalanine, protocatechuic acid, ocanine, nicotinic acid, L-tyrosine as antidepressants through pharmacokinetic analysis and drug likeness analysis using the SwissADME online application, then predict toxicity and brain penetration through 2D radar bioavailability results. using the ADMETLab online application. Compounds that met all parameters were L-phenylalanine and L-tyrosine with high GI absorption results, no P-gp inhibitors, no CYP1A2 inhibitors, no CYP2D6 inhibitors, yes BBB permeant and had a logKp value <2.5cm/s, no hepatotoxicity and no AMES toxicity, complies with Lipinski, Ghose, Veber regulations, bioavailability score 0.55, and showed the optimal range of values as an oral drug.